Aiding Reflective Navigation in a Dynamic Information Landscape: A Challenge for Educational Psychology - Bobrowicz, Katarzyna; Han, Areum; Hausen, Jennifer; Greiff, Samuel (Frontiers in Psychology, 2022)
Open access to information is now a universal phenomenon thanks to rapid technological developments across the globe. This open and universal access to information is a key value of democratic societies because, in principle, it supports well-informed decision-making on individual, local, and global matters. In practice, however, without appropriate readiness for navigation in a dynamic information landscape, such access to information can become a threat to public health, safety, and economy, as the COVID-19 pandemic has shown. In the past, this readiness was often conceptualized in terms of adequate literacy levels, but the contemporarily observed highest-ever literacy levels have not immunized our societies against the risks of misinformation. Therefore, in this Perspective, we argue that democratisation of access to information endows citizens with new responsibilities, and second, these responsibilities demand readiness that cannot be reduced to mere literacy levels. In fact, this readiness builds on individual adequate literacy skills, but also requires rational thinking and awareness of own information processing. We gather evidence from developmental, educational, and cognitive psychology to show how these aspects of readiness could be improved through education interventions, and how they may be related to healthy work-home balance and self-efficacy. All these components of education are critical to responsible global citizenship and will determine the future direction of our societies.